2018
DOI: 10.18203/2320-6012.ijrms20180006
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of cost of medical therapy in patients of metabolic syndrome: an observational study

Abstract: Background: The objective of the study was to analyze cost of medical therapy in patients of Metabolic syndrome.Methods: This was an observational study. The study was conducted by enrolling patients of the outpatient department of Medicine of Rajindra Hospital, Government Medical College, Patiala, Punjab. A total of 100 patients diagnosed with Metabolic syndrome were enrolled in the study. The total daily cost of the therapy was calculated by adding the direct cost of individual drugs taking in consideration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
(3 reference statements)
0
2
0
Order By: Relevance
“…The prevalence rate of MetS in children and adolescents has been estimated up to 19.2% globally in various populations 5 . According to previous reports, MetS had a huge financial burden on medical care systems every year 6,7 . Several risk factors, such as noticeable prevalence of obesity, 8,9 epidemiologic transition, 10 lifestyle changes, 11,12 and nutritional disorders, 13–15 led to the growing complication of MetS in the pediatric age group 16,17 which resulted in enormous concern over the last two decades.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence rate of MetS in children and adolescents has been estimated up to 19.2% globally in various populations 5 . According to previous reports, MetS had a huge financial burden on medical care systems every year 6,7 . Several risk factors, such as noticeable prevalence of obesity, 8,9 epidemiologic transition, 10 lifestyle changes, 11,12 and nutritional disorders, 13–15 led to the growing complication of MetS in the pediatric age group 16,17 which resulted in enormous concern over the last two decades.…”
Section: Introductionmentioning
confidence: 99%
“…The comorbidity and bidirectional associations between MetS and psychiatric disorders have been reported [ 6 , 7 , 8 , 9 , 10 , 11 ]. It has been reported that the coexistence of MetS and psychiatric disorders such as anxiety, depression, insomnia, and memory impairment take a huge share of the healthcare budget, so these conditions have to be be considered [ 12 , 13 , 14 , 15 ]. Despite this great impact on socio-economic burdens, most psychological disorder treatments in MetS have been neglected.…”
Section: Introductionmentioning
confidence: 99%